Effect of exposure to second-hand smoke from husbands on biochemical hyperandrogenism, metabolic syndrome and conception rates in women with polycystic ovary syndrome undergoing ovulation induction. Issue 4 (20th February 2018) - Li, Jian; Wu, Q; Wu, Xiao-Ke; Zhou, Zhong-Ming; Fu, Ping; Chen, Xiu-Hua; Yan, Ying; Wang, Xin; Yang, Zheng-Wang; Li, Wei-Li; Stener-Victorin, Elisabet; Legro, Richard S; et al.
Abstract: STUDY QUESTION: Does second-hand smoke (SHS) exposure from husbands have adverse effects on sex hormones, metabolic profiles, clinical phenotypes and fertility outcomes in women with polycystic ovary syndrome (PCOS) undergoing ovulation induction? SUMMARY ANSWER: SHS exposure is associated with worsened biochemical hyperandrogenism, higher incidence of metabolic syndrome and reduced conception rates in women with PCOS. WHAT IS KNOWN ALREADY: Smoking in women impairs fecundity at some stages of the reproductive process including folliculogenesis, embryo transport, endometrial angiogenesis and uterine blood flow. Yet little is known about the hazard of SHS exposure in women with PCOS. STUDY DESIGN, SIZE, DURATION: This study was a secondary analysis of the Polycystic Ovary Syndrome Acupuncture and Clomiphene Trial (PCOSAct), a large randomized controlled trial conducted at 27 hospitals from 2012 to 2015 in mainland China. PARTICIPANTS/MATERIALS, SETTING, METHODS: Out of 1000 women with PCOS, SHS exposure status were available in 500 women, of whom 271 women were non-exposed and 229 exposed to cigarette smoke (170 women ≤10 cigarettes per day as low-SHS exposed and 59 women >10 cigarettes per day as high-SHS exposed). We compared circulating sex steroids, glucose and lipid metabolism, metabolic syndrome and phenotypes, fertility and obstetric outcomes between non-exposed and exposed women. MAIN RESULTS AND THE ROLE OF CHANCE: Women exposed to SHS, compared to non-exposed women, had a higher serum total testosterone (1.7 vs 1.5 nmol/L, P = 0.01), free androgen index (5.7 vs 4.0, P = 0.001) and lower sex hormone binding globulin (30.1 vs 35.6 nmol/L, P = 0.03). Metabolic syndrome, but not other phenotypes, was more frequent in exposed women as compared to non-exposed women (21.8 vs 13.3%, adjusted odds ratio (OR)=1.66; 95% CI, 1.02–2.71, P = 0.04). Ovulation rates between exposed and non-exposed groups were not significantly different (76.9 vs 82.9%, adjusted OR=0.72; 95% CI, 0.45–1.15, P = 0.17). Conception rates were significant lower in the exposed group (26.6 vs 36.9%; adjusted OR=0.61; 95% CI, 0.41–0.91; P = 0.01), while clinical pregnancy and live birth rates showed a similar trend that was not statistically significant. Gestational age, birth weight and other obstetric outcomes were not affected by SHS exposure. LIMITATIONS, REASONS FOR CAUTION: Data on SHS exposure were missing in 50% of the women. We did not assay serum nicotine or cotinine levels to quantify the SHS exposure status. WIDER IMPLICATIONS OF THE FINDINGS: These data suggest that smoking partners of infertile women with PCOS who seek treatment should be advised to quit smoking. STUDY FUNDING/COMPETING INTEREST(S): Funding was provided by the National Public Welfare Projects for Chinese Medicine (201107005 and 200807002) and the National Clinical Trial Base in Chinese Medicine Special Projects (JDZX2012036 and 2015B009). There are no conflicts of interest. TRIAL REGISTRATION NUMBER: ClinicalTrial.gov number: NCT01573858 and chictr.org.cn number: ChiCTR-TRC-12002081.